Passivation by pyridine-induced PbI2 in methylammonium lead iodide perovskites. Issue 40 (23rd June 2020) - Cook, Andre; Jones, Timothy W.; Wang, Jacob Tse-Wei; Li, Hua; Atkin, Rob; Duffy, Noel W.; Donne, Scott W.; Wilson, Gregory J.
Abstract : Comparison of confocal fluorescence microscope (CFM) images at different excitation wavelengths show localized passivation effects by a pyridine treatment on a perovskite precursor, PbI2 . Abstract : Defects at discontinuities of the perovskite lattice limit the performance of the perovskite solar cell (PSC). Lead iodide (PbI2 ) and pyridine have been shown to passivate these defects. We treat methylammonium lead iodide (MAPbI3 ) films with pyridine solutions to investigate the effects of the two passivators. By comparing confocal fluorescence microscopy (CFM) images at 405 nm excitation and then at 559 nm excitation we demonstrate the pyridine treatment passivates and forms PbI2 crystallites which cause additional passivation.